Examining the Predictors of Mobile Addiction: Some Insights from Malaysia - Mohd Suki, Norazah; Mohd Suki, Norbayah (International Journal of Engineering and Technology, 2018)
This research aims to investigate the predictors of mobile addiction. The data was analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM) approach supported by Smart-PLS 2.0 to assess the hypothesis in the research model. The PLS-SEM technique revealed that there was a strong correlation between social networking sites (SNS) intensity and mobile addiction. Users have positively expressed that visiting SNS is part of their everyday activity as they tend to check their SNS almost every day. They have this perception that they will feel out of touch when they do not log into their SNS for a day. In addition, they feel as if they are part of the community of SNS on campus. Those with many SNS accounts have a strong tendency to install and use mobile social networking apps on their mobile phones to connect and communicate with others. These heavy users frequently use their mobile phone to log into their social network via preferred social networking apps and actively use it to check the SNS.Â The direction for future research is also presented.Â